Prescription and transcription errors in multidose‐dispensed medications on discharge from hospital: an observational and interventional study. Issue 1 (29th December 2011) - Alassaad, Anna; Gillespie, Ulrika; Bertilsson, Maria; Melhus, Håkan; Hammarlund‐Udenaes, Margareta
Abstract Background Medication errors frequently occur when patients are transferred between health care settings. The main objective of this study was to investigate the frequency, type and severity of prescribing and transcribing errors for drugs dispensed in multidose plastic packs when patients are discharged from the hospital. The secondary objective was to correct identified errors and suggest measures to promote safe prescribing. Methods The drugs on the patients' multidose drug dispensing (MDD) order sheets and the medication administration records were reconciled prior to the MDD orders being sent to the pharmacy for dispensing. Discrepancies were recorded and the prescribing physician was notified and given the opportunity to change the order. Discrepancies categorized as unintentional and related to the discharge process were subject to further analysis. Results Seventy‐two (25%) of the 290 reviewed MDD orders had at least one discharge error. In total, 120 discharge errors were identified, of which 49 (41%) were assessed as being of moderate and three (3%) of major severity. Orders with a higher number of medications and orders from the orthopaedic wards had a significantly higher error rate. Conclusion The main purpose of the MDD system is to increase patient safety by reducing medication errors. However, this study shows that prescribing and transcribing errors frequently occur when patients are hospitalized. Because the population enrolled in the MDD system is an elderly, physically vulnerable group with a high number of prescribed drugs, preventive measures to ensure safe prescribing of MDD drugs are warranted.